Peran Gapoktan dalam Peningkatan Pendapatan Petani Tanaman Hias (Studi Kasus Gapoktan “Tani Makmur” Kecamatan Tawangmangu Kabupaten Karanganyar) - Ferlita Azadhea Sasqia Putri; Joko Winarno; Retno Setyowati; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2024)
Ornamental plants are cultivated or grown for their aesthetic value, including the beauty of their flowers, leaves, or the entire plant. These plants are commonly found in home gardens or yards. The development of ornamental plant farming requires the role of agricultural institutions. Agricultural institutions play crucial role in modernization of agriculture. This study aims to understand institutional system, the role of agricultural institutions, and the impact of the Tani Makmur Farmer Group Association on ornamental plant farmers in Nglurah Village. This research employs a qualitative method with a case study approach in Nglurah Village. Informants were selected using purposive and snowball sampling techniques. The study involved 14 informants, including farmers group association stakeholders, agricultural officers, and ornamental plant traders. Validity was ensured through source and method triangulation, and data were analyzed using the Miles and Huberman analysis method. The results showed that Nglurah Village has an institutional system that supports the sustainability of ornamental plant farming. Farmers group association in Nglurah Village has procedures, management, and roles. Farmers group association in Tawangmangu Sub-district plays various roles in developing ornamental plant farming, including acting as a liaison between farmer groups and the government, providing farming capital, offering information or facilitation to groups, and establishing partnerships with other business units. These roles have social impacts on farmers, such as improved relationships and harmony, as well as economic impacts, including easier access to capital. There is a need to enhance each institution to ensure that the management system operates more effectively and achieves the goals of the Tani Makmur Farmer Group Association.